2015
DOI: 10.1097/igc.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cryoablation of Ovarian Cancer Metastasis to the Liver

Abstract: Our initial experience showed that cryoablation is a safe and effective ablative therapy, providing a high rate of local tumor control in ovarian cancer liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Our technical success rate of 94.6%, technique efficacy rate of 89.5% at 3 months, and local tumor progression rate of 23.3% compare favorably to the limited previously published data for percutaneous cryoablation of liver metastases, with technical success rates of 83 92% and technique efficacy rates of 47–85.4% [12, 18, 35, 36]. Previous studies of percutaneous cryoablation of HCC have reported technical success rates of 51–98.5% and technique efficacy rates of 69 75.8% [16, 22, 34].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our technical success rate of 94.6%, technique efficacy rate of 89.5% at 3 months, and local tumor progression rate of 23.3% compare favorably to the limited previously published data for percutaneous cryoablation of liver metastases, with technical success rates of 83 92% and technique efficacy rates of 47–85.4% [12, 18, 35, 36]. Previous studies of percutaneous cryoablation of HCC have reported technical success rates of 51–98.5% and technique efficacy rates of 69 75.8% [16, 22, 34].…”
Section: Discussionsupporting
confidence: 85%
“…For these reasons, cryoablation has been favored by some to treat hepatic masses, particularly those that are close to critical structures, such as the diaphragm, chest wall, heart, lung, gallbladder, and biliary tree [24, 33]. The majority of experience with percutaneous image-guided cryoablation has been in the treatment of HCC [16, 19, 22, 34] and, to a lesser extent, metastases [12, 19, 35]. However, to our knowledge, the overall safety and efficacy of percutaneous image-guided percutaneous cryoablation has not been defined in patients with a variety of primary and secondary hepatic tumors in a series using both CT and MRI guidance.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies from 2009 onward have demonstrated an improvement in disease-free survival and total survival of patients undergoing hepatic metastasectomy regardless of the types of primary neoplasias. 7,9,[20][21][22][23][24][25] Based on previous studies, the mean total survival for patients with stage IV ovarian epithelial cancer varied between 15 and 29 months, with a total survival of 20% at 5 years. 18 In the current study, diseasefree survival was better in patients with peritoneal seeding metastasis; however this result was nonsignificant and the overall survival analysis showed no difference among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rate after the first session of TACE was 58% at 1 year, 19% at 2 years, and 13% at 3 years. Recently, Gao et al 23 reported cryoablation in the treatment of patients with liver metastasis from OC. The LTP rate after ablation was 7.14%, and 1-year OS rate was 92.3%.…”
Section: Discussionmentioning
confidence: 99%